2019
DOI: 10.1678/rheology.47.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host-Guest Interaction on Swelling Behavior and Equilibrium Swollen State of Host-Guest Gel

Abstract: A Host-Guest gel is a supramolecular network formed by the dynamic crosslinking between β-cyclodextrin and adamantane molecules, and has a novel tough and self-healing properties. In our previous study, we showed that this gel has a topological permanent crosslinking in addition to the dynamic crosslinking, and these two types of crosslinking brings a unique swelling property such as attaining an equilibrium swollen state. In the present study, we examined the swelling behavior and equilibrium swollen states o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Non-covalent interactions occupy a pivotal role in living systems by determining the structure and function of a plethora of biomolecules such as DNA, RNA, and proteins. , They also enable specific transient recognition and binding of (macro)­molecules, rendering adaptive supramolecular assemblies. In particular, in the last 2 decades, the combination of supramolecular host–guest chemistry and hydrogel science has led to the development of materials featuring fascinating swelling, adhesive, shape-memory, and self-healing properties. , A large majority of these studies deal with supramolecular hydrogels in which host–guest interactions act as cross-link junctions to create single or double networks, while their stimuli-controlled dissociation results in a gel–sol transition. Recently, host–guest interactions have also been exploited to tune the swelling–shrinking properties of covalently cross-linked hydrogels. For example, methylated β-cyclodextrin was used as a host entity to trigger the swelling of chemically cross-linked poly­( N , N -diethylacrylamide) hydrogels bearing complementary hydrophobic adamantyl modules .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Non-covalent interactions occupy a pivotal role in living systems by determining the structure and function of a plethora of biomolecules such as DNA, RNA, and proteins. , They also enable specific transient recognition and binding of (macro)­molecules, rendering adaptive supramolecular assemblies. In particular, in the last 2 decades, the combination of supramolecular host–guest chemistry and hydrogel science has led to the development of materials featuring fascinating swelling, adhesive, shape-memory, and self-healing properties. , A large majority of these studies deal with supramolecular hydrogels in which host–guest interactions act as cross-link junctions to create single or double networks, while their stimuli-controlled dissociation results in a gel–sol transition. Recently, host–guest interactions have also been exploited to tune the swelling–shrinking properties of covalently cross-linked hydrogels. For example, methylated β-cyclodextrin was used as a host entity to trigger the swelling of chemically cross-linked poly­( N , N -diethylacrylamide) hydrogels bearing complementary hydrophobic adamantyl modules .…”
Section: Introductionmentioning
confidence: 93%
“…21,22 A large majority of these studies deal with supramolecular hydrogels in which host-guest interactions act as cross-link junctions to create single or double-networks while their stimulicontrolled dissociation results in a gel-sol transition. 23,24,25,26 Recently, host-guest interactions have also been exploited to tune the swelling-shrinking properties of covalently cross-linked hydrogels. For example, methylated -cyclodextrin was used as host entity to trigger the swelling of chemically cross-linked poly(N,N-ethylacrylamide) hydrogels bearing complementary hydrophobic adamantyl modules.…”
Section: Introductionmentioning
confidence: 99%
“…In water, hydrophobic interactions between βCD and Ad result in a stable inclusion complex, thus acting as a dynamic crosslink. Despite being a transient polymer network, the host-guest gel does not dissolve in water but remains in a swollen state, exhibiting gel-like properties 49) . Therefore, viscoelasticity and NMR measurements reveal the molecular origin of the host-guest gel properties 50) .…”
Section: Side-chain Crosslinked Transient Polymer Networkmentioning
confidence: 99%
“…112 Inoue and his coworker revealed that improvements in the mechanical properties of SC elastomers were derived from the viscoelastic behavior and relaxation mode of the movable cross-links. 115,116 Notably, the advantage of the fifth method is an easy preparation of movable cross-linked materials through the polymerization of vinyl monomers. By expanding the fifth method, the combination of two dissimilar polymers using movable cross-links will improve the toughness and Young's modulus of the material.…”
Section: Introductionmentioning
confidence: 99%